2010
DOI: 10.1093/jnci/djq001
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Human Papillomavirus Persistence and Cervical Intraepithelial Neoplasia Grade 2/3: Critical Role of Duration of Infection

Abstract: The rate of new infections declines with age, and new infections typically do not progress to CIN 2 or worse disease in older women; thus, overall potential benefit of prophylactic vaccination or frequent HPV screening to prevent or detect new carcinogenic HPV infections at older ages is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
298
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(328 citation statements)
references
References 48 publications
23
298
1
6
Order By: Relevance
“…23,43 Clearance In this 12-month follow-up study, the overall clearance proportion of the newly detected (i.e., incident) hr-HPV and lr-HPV infections was 61.2% and 69.0%, respectively. Confirming the finding that most incident HPV types are not detected 6-12 months later.…”
Section: Incidencementioning
confidence: 77%
See 1 more Smart Citation
“…23,43 Clearance In this 12-month follow-up study, the overall clearance proportion of the newly detected (i.e., incident) hr-HPV and lr-HPV infections was 61.2% and 69.0%, respectively. Confirming the finding that most incident HPV types are not detected 6-12 months later.…”
Section: Incidencementioning
confidence: 77%
“…Therefore, we can only measure presumed incidence because it is presently impossible to distinguish a new infection from an accidental pick-up or reactivation of a latent infection. 13,43 Although women aged 24-29 years had a higher incidence rate compared to 18-23 years old women, age was not an independent risk factor for HPV incidence. When analyzing the age groups compared to the variable 'having a new sexual partner during follow-up', women in the age group 24-29 years have more new sexual partners compared to the younger women (p-value ¼ 0.145).…”
Section: Incidencementioning
confidence: 95%
“…It has been shown that different oncogenic HPV genotypes5 have different cross‐sectional6 and longitudinal7 strengths of association with high‐grade CIN and invasive cervical cancer. In particular, HPV16 has been shown to be strongly associated with both high‐grade CIN and invasive cervical cancer 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Only a very small fraction (about 10%) of women will develop viral persistence, and only some of those who are chronically infected with a high-risk HPV type will have a high risk of infection progressing to neoplastic lesions (9). The average total time from infection with a carcinogenic HPV type to the occurrence of invasive cervical cancer is 25-30 years or longer (11). HPV infection is basically a sexually transmitted disease.…”
Section: Introductionmentioning
confidence: 99%